Spindle Cell Lipoma of the Spermatic Cord: A Case Presentation and Literature Review of a Urologic Rarity and Radiologic Mimic of Malignant Liposarcoma - Dahmen, Aaron; Juwono, Timothy; Russo, Nicholas W.; Patel, Trushar (Frontiers in Urology, 2022)
Background Spindle cell lipomas are uncommon variants of typical lipomas, and presentation within the spermatic cord is exceedingly rare. Only three other cases have been reported in medical literature. Case Presentation We present the fourth case of spindle cell lipoma of the spermatic cord, which in this particular case had imaging findings suggestive of a malignant liposarcoma prompting radical orchiectomy. Histological investigation later concluded that this represented a benign, spindle cell lipoma of the spermatic cord as evidence by positive CD34 staining and microscopic analysis. Conclusion Although this particular variant of lipoma is rare, it is the hope that these findings contribute to the continued study of this disease process and can potentially prompt further evaluation prior to radical orchiectomy to limit patient morbidity.